Mewujudkan Perajin Gerabah yang Mandiri Melalui Program - Rubiyatno Rubiyatno; Josephine Wuri; Lisia Apriani (Universitas Sanata Dharma, 2018)
The purpose of this community service is to enhance entrepreneurial motivation, improve understanding of human resource optimization, improve partners' understanding of business plans and also produce business plan documents as business development plans and improve financial management. As a result, innovative product designs have the value of selling by utilizing information technology, understanding and entrepreneurship skills in their fields, enhancing the ability of craftsmen in using the Internet network for expansion of marketing, improving financial management through cash flow, and the ability of partners to operate a financial-based application program a simple computer. Participatory approaches are used for partners to actively participate in all activities from start to finish. After conducting discussion with Partners 1 and 2, we provided the necessary training and mentoring to help overcome the weaknesses of Partners 1 and Partners 2, pottery craftsmen in Panjangrejo Pundong area, Bantul. After completing the program, it can be concluded that Partner 1 and Partner 2 were extremely enthusiastic in this activity due to the desire to be good at developing their business and all targeted indicators have been achieved, for example, customer identification and availability of production equipment.